Rancang Bangun Sistem Informasi Penjualan Peternakan Kambing Berbasis Website menggunakan Metode Rapid Application Development (RAD): Studi Kasus Herman Farm - Siti Aisyah; Mardiah Mardiah; Muhammad Khaibar Putra Adithia (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2026)
This study aims to design and develop a web-based sales information system for a goat farming business at Herman Farm using the Rapid Application Development (RAD) method. The identified problems include manual transaction recording, stock management, and sales reporting processes, which are inefficient, prone to errors, and unable to provide real-time data access. The RAD method is selected due to its ability to accelerate system development through an iterative approach and active user involvement in each stage, including requirements planning, system design, construction, and implementation. Data collection techniques include observation, interviews, and literature studies. The developed system provides features for managing goat data, sales transactions, customer management, and integrated sales reporting within a web-based platform. The results show that the system improves efficiency in data management and transaction processes, while producing more accurate, structured, and accessible reports. Therefore, this system can assist Herman Farm in optimizing its sales operations and expanding its online marketing reach.